Improving Students’ Motivation and Psychology in Speaking Arabic through Dubbing Japanese Anime to Arabic - Taufik Nurrohman; Yunita Yunita; Moh. Paris Fauzi Sawedi; Cahya Adi Prabowo (LISANIA: Journal of Arabic Education and Literature, 2022)
This article aims to determine the level of motivation and to build students' interest in speaking Arabic with Japanese to Arabic anime voiceover media, as well as to overcome students' psychological problems. A total of 90 students aged 15-18 years in three educational institutions in Java Island participated in the study. The data were calculated quantitatively descriptively, processed by the Kolmogorov normality test using SPSS 26 and made and analyzed a comparison table of pretest and posttest scores from the HARS (Hamilton Anxiety Rating Scale) questionnaire. The results confirmed that there was a significant change in the results of the HARS questionnaire table and the Kolmogorov value with a mean value of 44.04 which was greater than the hypothesis, which was 30.00. The implications of this research can be used as an alternative learning media in increasing motivation and overcoming students' negative psychology in learning Arabic in Indonesia.